1996
DOI: 10.1203/00006450-199604000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prolonged Modification of Cerebral Temperature on Outcome after Hypoxic-Ischemic Brain Injury in the Infant Rat

Abstract: Hypoxic-ischemic injuries can evolve over several days, and recent studies suggest that further neuronal death may occur 6 to 72 h later. Because cerebral temperature is an important determinant of outcome during the primary injury, we investigated the effect of temperature, on outcome, during the later phases of injury. Hypoxic-ischemic injury was induced in 21-d-old rats by unilateral ligation of the right carotid artery followed by exposure to 15 min of hypoxia of 8% O2 at 34 degrees C. Cerebral temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(60 citation statements)
references
References 34 publications
0
60
0
Order By: Relevance
“…For example, in unanesthetized infant rats subjected to moderate hypoxia-ischemia, mild hypothermia (2 to 3°C decrease in brain temperature) for 72 hours from the end of hypoxia prevented cortical infarction, while 6 hours of cooling had an intermediate effect. 70 In the same model, however, a greater reduction in body temperature, of 5°C, for 6 hours, starting immediately after the insult, gave significant neuroprotection both after 1 and 6 weeks survival as well as neurobehavioral improvement. 75 Similarly, in anesthetized piglets exposed to either hypoxia with bilateral carotid ligation or to hypoxia with hypotension, either 12 hours of mild whole body hypothermia (35 o C) or 24 hours of head cooling with mild systemic hypothermia started immediately after hypoxia prevented delayed energy failure, 76 reduced neuronal loss 55,77 and suppressed post-hypoxic seizures.…”
Section: The 'Pharmacodynamics' Of Hypothermiamentioning
confidence: 89%
See 1 more Smart Citation
“…For example, in unanesthetized infant rats subjected to moderate hypoxia-ischemia, mild hypothermia (2 to 3°C decrease in brain temperature) for 72 hours from the end of hypoxia prevented cortical infarction, while 6 hours of cooling had an intermediate effect. 70 In the same model, however, a greater reduction in body temperature, of 5°C, for 6 hours, starting immediately after the insult, gave significant neuroprotection both after 1 and 6 weeks survival as well as neurobehavioral improvement. 75 Similarly, in anesthetized piglets exposed to either hypoxia with bilateral carotid ligation or to hypoxia with hypotension, either 12 hours of mild whole body hypothermia (35 o C) or 24 hours of head cooling with mild systemic hypothermia started immediately after hypoxia prevented delayed energy failure, 76 reduced neuronal loss 55,77 and suppressed post-hypoxic seizures.…”
Section: The 'Pharmacodynamics' Of Hypothermiamentioning
confidence: 89%
“…93 The most likely explanation is that the duration and / or degree of hypothermia may have been inadequate as suggested by the finding that cooling by 5°C for 6 hours 75 or 72 hours of very mild cooling in infant rats were associated with long-term improvement after carotid occlusion and hypoxia. 70 Subsequent studies both in the 7 day rat and in adult species have confirmed that a sufficiently prolonged phase of moderate cooling can be associated with persistent behavioral and histological protection for many weeks and months. 75,83,84,87,94 -96 Broadly, these studies tend to suggest that the later cooling is started, the more prolonged the treatment needs to be for neuroprotection.…”
Section: The 'Pharmacodynamics' Of Hypothermiamentioning
confidence: 96%
“…Studies in newborn and fetal models of hypoxiaischemia similarly suggest that delayed hypothermia reduces injury (21,22,39). One study (39) in 21-day-old rats illustrates that 72 h of cooling is more efficacious than a 6-h duration and that persistent (3 weeks) cortical neuroprotection occurs with protracted hypothermia.…”
Section: Figmentioning
confidence: 99%
“…One study (39) in 21-day-old rats illustrates that 72 h of cooling is more efficacious than a 6-h duration and that persistent (3 weeks) cortical neuroprotection occurs with protracted hypothermia. As with the adult studies, the optimal pattern of hypothermia has yet to be defined.…”
Section: Figmentioning
confidence: 99%
“…Another treatment, which has been studied widely, initially in animals 23,24 and then in neonates, [25][26][27][28][29][30] is therapeutic hypothermia. The reduction of body temperature by 3ºC to 5ºC less than normal body temperature during reperfusion before secondary energy failure occurs, can reduce cerebral injury.…”
Section: Treatmentmentioning
confidence: 99%